Pillars of Strength in The Nuclear Negotiations between Iran and The Great Powers (5+1) - Jihad Aldeen Albadawi (European Scientific Journal, ESJ, 2016)
This research examines the causes as well as motives that contributed to a landmark nuclear agreement with the U.S. and the Islamic Republic of Iran. It also finds out a combination of internal factors in Iran, which in turn led to that agreement. An examination of these influencing factors, we can ensure that the United States needs a comprehensive and strategically diplomatic approach to dealing with the Islamic Republic of Iran because of the threats that Iran poses to U.S. interests in the region. More generally, the window of opportunity for achieving a diplomatic breakthrough is needed because of Iran’s progress in developing its military capabilities, an increase in Iran’s regional standing and capacity to attack any great power. Therefore, the west and Obama's administration believe that the international parties must adopt a comprehensive approach to diplomacy with Iran over the nuclear issue as it happened in the Vienna agreement, which gave Iran all its nuclear rights. The growing influence of Iran in the region, and at a time when the Middle East witnesses the gradual decrease of US influence have forced the United States to make a “grand bargain” with Iran—that is, an overarching framework in which outstanding bilateral differences are resolved, which resulted in the Vienna agreement that guarantees the peaceful nuclear rights to the Islamic republic under strategically meaningful limits on its nuclear activities.